Investigating Learner Silent and Verbal Responses to Tasks - Dat Bao; Yongde Ye (International Journal of Language Teaching and Education, 2020)
This article reports a study on EFL/ESL learner perceptions of classroom tasks with reference to verbal or non-verbal participation, that is, how much speech and silence would be employed in response to a rage of task types. Data were collected from 260 learners from Indonesia and the Philippines. The article begins by explaining why silence and speech are the focus of the discussion. Secondly, it shares the literature review on how silence works in language learning and why it deserves a place in classroom teaching. Thirdly, it highlights classroom tasks that trigger silent processing and explain why this is the case. Finally, there are recommendations for task design in which similar activity types are introduced to assist the learning of reflective students.